(untitled) (International Journal of Innovative Research in Engineering & Management, 2024)
Religion plays a valuable role as an essential institution in Nation-Building. Studies of Nation-Building movements throughout the world recognize religion as a major driving force of Nation Building. In the history of Korea, the colonial period of Japan (1910-1945) has been marked as one of the darkest periods, and this disaster has become a backbone to growing-up Christianity in Korea.Different people and groups approached nation-building in distinct ways resulting in a variety of nationalistic moments. Christianity as a Korean institution played an integral role in shaping the view of Christians and the church and their actions toward nationalism. Under the Japanese colonial era, the people of Korea had to face phycological injuries, injustices, inequalities, and impoverishment, and it has also flourished the existence of Christianity and its political environment in Korea. Christianity started to gain popularity and became identified as a reliance with which the people of Korea hoped to liberate themselves from the dark period of Japanese Colonial rule.The presence of Christianity was pronounced at every level of anti-Japanese organizations, and they started to participate actively in the independence movement against Japanese rule. On the way to nation-building, Korea needed to adopt elements of Western culture to strengthen the nation.This article provides insights into the nation-building carried out by Christianity in Korea during the colonization period of Japan. Although it is not a depth study of Christianity in Korea, it’s role in nation building. It will also try to find the links between Christianity and nation-building in Korea.